Daily field checking list by Walter Rosene, June 25, 1939 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed at Ledges State Park by Walter Rosene and Myrle L. Jones, June 25, 1939. Also notes he was hunting for a Bell's Vireo nest but did not find one. Plustek--flatbed